2017
DOI: 10.1074/jbc.m116.772897
|View full text |Cite
|
Sign up to set email alerts
|

Chicken galectin-1B inhibits Newcastle disease virus adsorption and replication through binding to hemagglutinin–neuraminidase (HN) glycoprotein

Abstract: Galectin-1 is an important immunoregulatory factor and can mediate the host-pathogen interaction via binding glycans on the surface of various viruses. We previously reported that avian respiratory viruses, including lentogenic Newcastle disease virus (NDV), can induce up-regulation of chicken galectin (CG)-1B in the primary target organ. In this study, we investigated whether CG-1B participated in the infectious process of NDV in chickens. We demonstrated that velogenic NDV induced up-regulation of CG-1B in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Vero cells were cultured overnight in 96-well microplates (Corning, USA) (10 5 cells/well). For the adsorption assay, each strain was incubated in cells at a multiplicity of infection (MOI) of 1 for 1 h at 4°C with three replicates (Fang et al, 2010;Sun et al, 2017). After two washes with PBS, the microplates were fixed with methanol and 1% hydrogen peroxide for 30 min, and then permeabilized with 0.2% Triton X-100 for 10 min at room temperature.…”
Section: Adsorption and Internalization Assessments Using A Cellular mentioning
confidence: 99%
“…Vero cells were cultured overnight in 96-well microplates (Corning, USA) (10 5 cells/well). For the adsorption assay, each strain was incubated in cells at a multiplicity of infection (MOI) of 1 for 1 h at 4°C with three replicates (Fang et al, 2010;Sun et al, 2017). After two washes with PBS, the microplates were fixed with methanol and 1% hydrogen peroxide for 30 min, and then permeabilized with 0.2% Triton X-100 for 10 min at room temperature.…”
Section: Adsorption and Internalization Assessments Using A Cellular mentioning
confidence: 99%
“…the hN protein is a capsid protein that attaches itself firmly to the viral membrane, thus making it very difficult to isolate and purify from infected cells (Shahid et al, 2015). immunization with recombinant hN protein has been attempted many times to study protective immune responses in chickens (Boursnell et al, 1990;Edbauer et al, 1990;Sun et al, 2008;Su et al, 2011). in the current study, an attempt was made to evaluate the immune response against recombinant hN in chickens at different time intervals; the stimulation of the immune response indicated that the recombinant hN protein had properly folded.…”
Section: Discussionmentioning
confidence: 96%
“…the poultry industry is highly negatively affected by NdV, a member of the genus Avulavirus in the family Paramyxoviridae. NdV is an enveloped virus with a nonsegmented, linear, negative-sense, single-stranded RNA genome (Shahid and daniell, 2016;Sun et al, 2017). the total NdV genome comprises nearly 15,186 nucleotides (Jin et al, 2017) that encode 6 genes, including two transmembrane glycoproteins, a hemagglutinin-neuraminidase protein (hN) and a fusion protein (f).…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of this compound on monolayer cells might prevent viral adsorption. NDV bound to chicken RBCs through the HN binding site [ 35 ]. The results of the hemagglutination inhibition assay suggested that polyphenon-60 might bind to NDV, thereby inhibiting the HA activity of the virus.…”
Section: Discussionmentioning
confidence: 99%